Malaysian Halal Standard (Ms1500:2004) : Do Halal Food Manufacturers Have Intention To Be Certified ? - S. M. Mohiyaddin, Mohamad Ijaz (2006)
The Malaysian government has a vision of becoming a global halal hub. In line with this MS1500:2004 Halal Standard was introduced as extension to the existing halal logo and certification.